Tingkat Pengetahuan tentang Cairan Tubuh dan Status Hidrasi pada Mahasiswa Fakultas Kedokteran Universitas Sumatera Utara - Lubis, Nenni Dwi Aprianti; Sitanggang, Theresia; Nasution, Fitriyani; Sasmita, Hidayat; Amelia, Sri (Buletin Farmatera, 2022)
Water is an essential nutrient needed by the body. Humans cannot produce water to meet their bodily fluid needs. Data in 2016 on fluid intake in Indonesia shows that 22% of children aged 4-9 have deficiency fluids, 21% in children aged 10-17 years, and 28% at 18-65. This study aimed to analyze the relationship between the level of knowledge about body fluids and hydration status in medical students of the Faculty of Medicine, University of North Sumatra. This type of research is analytic with a cross-sectional design and using a simple random sampling technique with 99 students as the research sample. The variables studied were the level of knowledge measured by a questionnaire and the hydration status obtained by comparing the urine color with the PURI card. The results showed that most of the samples had a moderate level of knowledge about fluids (51.5%) and were dehydrated (48.5%). From the results of statistical tests using Chi-squared with ? value = 0.05, it is known that there is a relationship between the level of knowledge and hydration status (p = 0.034).